MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR IPS TERPADU DI MTS NEGERI 1 PASURUAN - Rifandi, Muhammad Sofi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2018)
The purposes of the research are: (1) To describe the implementation of the utilization of learning media of Integrated Social Studies Subjects of the Students of Class VII at Public Junior High School 1 of Pasuruan. (2) To know the learning result of the utilization of learning media Integrated Social Studies Subjects of the Students of Class VII at Public Junior High School 1 of Pasuruan. (3) To describe and explain the problems of the utilization of Integrated Social Studies Subjects of the Students of Class VII at Public Junior High School 1 of Pasuruan To achieve the objectives above, it had used descriptive qualitative approach for three months. The key instruments are the researcher, and the collection techniques used observation and interviews. Data can be used by reducing relevant data, exposing data and drawing conclusions. The results of the research showed that (1) the implementation of learning media utilization, the teacher uses audiovisual media using LCD at school, the teacher can use the learning media by using the photo or the video about the learning material that has been explained. (2) the student learning outcomes after utilizing the audiovisual media on integrated Social Science subjects are very well. The average student gets a lot of good results with a value of 8.5. (3) the supporting factors are the facilities of adequate infrastructure, motivation and work ethics of educators in using learning media based on audiovisual, the student’s discipline in following the teaching and learning activities in the class. The inhibiting factors are the lack of awareness of educators in the utilization of learning media based on audiovisual at school.Keywords: audiovisual; learning outcomes